2003
DOI: 10.1007/s10198-002-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cost-effectiveness over time

Abstract: We analysed the factors influencing cost-effectiveness of a health care intervention over time using economic evaluations of erythropoietin as a case study. The analytical framework of a study conducted in 1990 was used to revisit the cost-effectiveness of erythropoietin. Study variables were updated to 2000 using meta-analysis, published sources, and expert opinion. After 10 years of further experience with the use of erythropoietin the cost-effectiveness ratio now falls within the range considered acceptable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…One study found hospital stay to decrease with higher hemoglobin targets and found that strategy to be dominant [16], whereas a second study found higher targets to be associated with an increase in hospitalization risk and found the strategy to be dominated by lower targets [13]. A final study found that length of stay was greatly reduced with the use of ESAs (1.83 vs. 4.91 days) and found ESAs to be cost effective, given typical thresholds (USD <50,000/QALY) [17]. All of the studies assumed that the use of ESAs was associated with an increase in quality of life in comparison to no ESA or RBCT and that higher targets were associated with increased quality of life, with larger utility gains from low and medium targets in comparison to no ESA, having less incremental benefit to overall utility, as hemoglobin targets reached over 11-12 g/dl in studies that considered higher hemoglobin targets [13,15].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study found hospital stay to decrease with higher hemoglobin targets and found that strategy to be dominant [16], whereas a second study found higher targets to be associated with an increase in hospitalization risk and found the strategy to be dominated by lower targets [13]. A final study found that length of stay was greatly reduced with the use of ESAs (1.83 vs. 4.91 days) and found ESAs to be cost effective, given typical thresholds (USD <50,000/QALY) [17]. All of the studies assumed that the use of ESAs was associated with an increase in quality of life in comparison to no ESA or RBCT and that higher targets were associated with increased quality of life, with larger utility gains from low and medium targets in comparison to no ESA, having less incremental benefit to overall utility, as hemoglobin targets reached over 11-12 g/dl in studies that considered higher hemoglobin targets [13,15].…”
Section: Resultsmentioning
confidence: 99%
“…All seven studies follow a health-care payer perspective. Five studies compared ESA treatment to routine blood transfusion [13,15,17,18,19], and three compared to lower hemoglobin targets [13,14,17]. The characteristics of the included studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations